NOBLE GASES IN D'ORBIGNY, SAHARA 99555 AND D'ORBIGNY GLASS-EVIDENCE FOR EARLY PLANETARY PROCESSING ON THE ANGRITE PARENT BODY - Busemann H.; Lorenzetti S.; Eugster O. (My University, 2006)
We analyzed the spallogenic, trapped, fissiogenic and radiogenic noble gas components in various bulk samples of the angrites D'Orbigny and Sahara 99555 as well as in glass separates of D'Orbigny. The D'Orbigny glass samples show hints of solar-like noble gases, as deduced from the trapped elemental and Ne isotopic compositions; the bulk samples do not contain detectable amounts of trapped gases. These observations indicate that D'Orbigny experienced a complex history shortly after its formation 4.56 Ga ago. The glass of D'Orbigny most likely represents magma that rose from the interior of the angrite parent body (APB) and was quenched near the surface. Hence, the APB may contain-similar to the interior of Earth and Mars-solar noble gases. This would call into question the suggested trapping mechanism for solar noble gases in the Earth and Mars, which involves the solution of early atmospheres into magma oceans, due to the APB's inability to retain a primordial atmosphere. The first detection of-possibly parentless-radiogenic excess 129Xe and solar noble gases in the glass of D'Orbigny indicates that the interior of APB degassed to a lesser degree than the outer regions. Therefore primordially trapped, fossil 129I was kept. The APB was not completely devolatilized. Sahara 99555 yields a cosmic-ray exposure age of 6.8 ± 0.3 Ma, while D'Orbigny was exposed to cosmic rays for 11.9 ± 1.2 Ma. Both ages are different than those found in the other angrites. Hence, the angrites analyzed so far sampled surface material from the APB that was ejected in at least five events. In contrast to the bulk sample, the D'Orbigny glass separates yield concordant ages of only 3.0 ± 1.1 Ma, apparently suggesting a pre-exposure of the host material. However, such a scenario is unlikely, due to very similar Mn-Cr ages found in the bulk and glass of D'Orbigny. Most likely, this discrepancy is the result of additional, secondary gas-free glass. Such glass might have been formed during the meteorite's entry into the Earth's atmosphere. Isotopically anomalous Xe due to the decay of 247Cm has not been found. The presence of 247Cm in glass of D'Orbigny has been suggested based on Pb isotope constraints. © 2006 Elsevier Inc. All rights reserved.